ANALISIS PENGARUH PRODUK DOMESTIK BRUTO, TINGKAT INFLASI, DAN NILAI TUKAR RUPIAH ATAS US DOLLAR TERHADAP IMPOR INDONESIA PERIODE 2010.Q1 – 2017.Q4 - Jusmer Sihotang; Yabes Gulo (LPPM Universitas HKBP Nommensen, 2020)
This study aims to analyze the effect of Gross Domestic Product (GDP), inflation rate, and the Indonesian Rupiah (IDR) exchange rate to US Dollar on Indonesian imports. The study uses multiple regression equation models using secondary time series data in the period of 2010.Q1 to 2017.Q4. The results showed that the coefficient sign of each regression independent variable (real Gross Domestic Product, inflation rate, and Indonesian Rupiah (IDR) exchange rate on US Dollar) were in accordance with theoretical expectations, and all of these independent variables could explain for 60.3 percent of the diversity of the dependent variable namely imports Indonesia. Both simultaneously and individually all these independent variables significantly influence Indonesia's imports at the level of α = 1%. The real Gross Domestic Product and inflation rate have a positive and significant effect on Indonesian imports, while the Indonesian Rupiah (IDR) exchange rate on US Dollar has a negative and significant effect on Indonesia's imports. Based on the results of the study, in order to control Indonesia's imports in the future, a policy should be guarantee the availability of various imported substitution products, easy to obtain, and can compete with imported products. Thus the impact of the increase in Gross Domestic Product, an increase in the inflation rate, and the appreciation of the rupiah against the increase in Indonesian imports will be controlled.